Zakat dan Wakaf dalam Perspektif Hukum Islam: Regulasi dan Implementasinya di Indonesia - Dina Safitri; Ghina Aulia Rizky; Mita Mita; Nabila Anggraini; Ali Murtadho (STIKes Ibnu Sina Ajibarang, 2025)
This article comprehensively discusses the concept of zakat and waqf from the perspective of Islamic law, as well as its regulations and implementation in Indonesia. Zakat as a religious obligation has the function of purifying property and life, while waqf is a form of almsgiving which aims to provide sustainable benefits for society. In the context of national regulations, zakat is regulated in Law Number 23 of 2011, while waqf is regulated through Law Number 41 of 2004 and various implementing regulations. Zakat management is carried out by the National Zakat Amil Agency (BAZNAS) and the Zakat Amil Institute (LAZ), while waqf is managed by officially registered nazhir. This article highlights the importance of transparency, accountability and professionalism in the management of zakat and waqf funds, as well as the urgency of building synergy between the two to support sustainable social and economic development programs. Optimizing zakat and waqf as instruments for community empowerment requires strengthening institutional capacity, supporting adaptive regulations, as well as increasing literacy and community participation.